Artificial Light in Medieval Churches - Ivanovici, Vladimir,; Sullivan, Alice Isabella, (East Central and Eastern Europe in the Middle Ages, 450-1450 ;, 2026)
This volume examines the economy of artificial light in medieval churches across Eastern Europe, the Mediterranean region, and the broader medieval spheres. Whether innovative or inspired by the more established Latin and Byzantine traditions, the chapters explore local customs in order to understand how artificial light was used in ecclesiastical spaces, and how it brought together aspects of the architecture, decoration, objects, and rituals, while implicating the celebrants and the faithful gathered within the spaces. This volume complements the publication Natural Light in Medieval Churches (Brill, 2023). Contributors are: Anna Adashinskaya, Giulia Arcidiacono, Jelena Bogdanović, Debanjana Chatterjee, Aleksandar Čučaković, Dušan Danilović, Thomas E. A. Dale, Magdalena Dragović, Diego R. Fittipaldi, Evan Freeman, Leslie Forehand, Jacob Gasper, Branka Gugolj, Vera Henkelmann, Vladimir Ivanovici, Charles Kerton, Daniela Mondini, Robert S. Nelson, Marko Pejić, Teresa Shawcross, Alice Isabella Sullivan, Danijela Tešić Radovanović, and Travis Yeager.